Testing of worn face mask and saliva for SARS-CoV-2 - Wang, Xiaoling; Thwin, Ohnmar; Haq, Zahin; Dong, Zijun; Tisdale, Lela; Fuentes, Lemuel Rivera; Grobe, Nadja; Kotanko, Peter (Frontiers in Public Health, 2023)
Background: Exhaled SARS-CoV-2 can be detected on face masks. We compared tests for SARS-CoV-2 RNA on worn face masks and matched saliva samples.: We conducted this prospective, observational, case-control study between December 2021 and March 2022. Cases comprised 30 in-center hemodialysis patients with recent COVID-19 diagnosis. Controls comprised 13 hemodialysis patients and 25 clinic staff without COVID-19 during the study period and the past two months. Disposable 3-layer masks were collected after being worn for four hours together with concurrent saliva samples. ThermoFisher COVID-19 Combo Kit (A47814) was used for RT-PCR testing.Results: Mask and saliva testing specificities were 99% and 100%, respectively. Test sensitivity was 62% for masks, and 81% for saliva (p=0.16). Median viral RNA shedding duration was 11 days and longer in immunocompromised versus non-immunocompromised patients (22 vs 11 days; p=0.06, log-rank test).While SARS-CoV-2 testing on worn masks appears to be less sensitive compared to saliva, it may be a preferred screening method for individuals who are mandated to wear masks yet averse to more invasive sampling. However, optimized RNA extraction methods and automated procedures are warranted to increase test sensitivity and scalability. We corroborated longer viral RNA shedding in immunocompromised patients.